2022
DOI: 10.3390/nu14102034
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Diet and Mortality, Disability, and Dementia: Evidence from the Ohsaki Cohort Study

Abstract: The Japanese dietary pattern has long been discussed as one of the factors behind the longevity of Japanese people. However, the health benefits of the Japanese dietary pattern have not been fully elucidated. We published the first report in the world regarding the relation between the Japanese dietary pattern and cardiovascular disease mortality in 2007 using cohort studies including Japanese residents of Ohsaki City, Miyagi Prefecture, Japan. Since then, we have developed the Japanese Diet Index (JDI) that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The traditional Japanese diet has been known to be healthy ( 5 , 6 ). However, westernization of the Japanese diet and other lifestyle factors has led to a gradual increase in the Japanese population with obesity and obesity-related diseases since the 1960s ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional Japanese diet has been known to be healthy ( 5 , 6 ). However, westernization of the Japanese diet and other lifestyle factors has led to a gradual increase in the Japanese population with obesity and obesity-related diseases since the 1960s ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese population included in the Seven Countries Study showed, together with the Mediterranean population, a reduced incident CVD and total mortality when compared with populations from the USA and Finland, results that have been confirmed in recent studies by Shirota et al [ 42 ]. Recent studies have also shown an inverse association of a higher adherence to the Japanese dietary pattern with a lower risk of disability and incident Alzheimer’s disease [ 43 ]. In summary, available evidence suggests that the traditional Japanese dietary pattern can be considered one of the determinants of the exceptional and healthy longevity observed in the Japanese population versus Western populations.…”
Section: Japanese Dietmentioning
confidence: 99%
“…Kobayashi et al [ 11 ] reported from the Japan Public Health Center-based Prospective Study (JPHC) that the greater the diversity of foods, including fruit and soy consumed, the lower the total mortality and mortality from major diseases. Many studies have reported that rice, fish, and soy products are effective in preventing obesity [ 12 ], ischaemic heart disease [ 13 – 15 ], and other diseases [ 15 19 ]. A Japanese dietary pattern high in these foods may be beneficial for health.…”
Section: Introductionmentioning
confidence: 99%